UNDERSTANDING THE 7 KEY PROHIBITIONS IN ISLAMIC TRADE PRACTICES - Iin Candrawati; Shofa Robbani (Nurul Jadid University, 2025)
This paper aims to identify and analyze the seven main prohibitions in Islamic trade practices: riba (usury), gharar (uncertainty), tadlis (deception), maysir (gambling), ghabn (exploitation), najsh (price manipulation), and jahalah (ignorance). The research employs descriptive and qualitative methods, focusing on an extensive review of relevant literature as the primary source of data. The findings indicate that violations of these prohibitions result in economic injustice and social harm, undermining the principles of fairness and balance advocated by Islamic teachings. By understanding and avoiding these forbidden practices, Muslim business practitioners can promote a just and Sharia-compliant economic system. The study highlights the importance of education and awareness to ensure the integration of Islamic principles into business activities.